Uniscaff stairfold / Nurhazwani Mohd Hasnin and Mohd Fareh Majid - Mohd Hasnin, Nurhazwani; Majid, Mohd Fareh (2023)
This research project explores the pivotal role of scaffolding in the construction industry, with a particular focus on its challenges, safety considerations, components, and recent technological advancements. The study underscores the paramount importance of adhering to safety regulations and guidelines to ensure the well-being of workers and prevent accidents. Emphasising the significance of regular inspections, maintenance, and proper training for workers, the research aims to uphold the integrity of scaffolding structures. In addition to addressing common issues related to scaffolding, the study delves into innovative solutions, with a notable highlight on the Uniscaff Stairfold concept. This revolutionary system incorporates folding mechanisms, attachable components, and modular designs, significantly enhancing efficiency and convenience in staircase scaffolding. The Uniscaff Stairfold concept represents a ground-breaking advancement in scaffolding technology, offering convenience, flexibility, and safety to construction projects. Furthermore, the research explores technological advancements that have impacted scaffolding practices.